Perceived Risk as a Mediator Between Brand Trust, Perceived Fit, and Brand Extension Success: Case Study of China Time-honored Brand - Lu, Change; Pulpetch, Thitima; Li, Liou-Yuan (Bright Publisher, 2024)
This study aimed to explore the causal relationship and impact of perceived risk on brand extension success, with a particular focus on insights drawn from China Time-honored brand. The primary research question addressed in this study is: Does perceived risk mediate the effects of brand trust and perceived fit on brand extension success? Based on perceived risk theory, categorization theory, this study constructs a research model by adopting China time-honored brand as the research subject. The study collected 605 valid survey responses using a self-filled questionnaire, employing a combination of purposive and random sampling methods in the location of the parent brands. Quantitative analysis was conducted using partial least squares structural equation modeling (PLS-SEM) to test 4 research hypotheses. The findings indicate that: In the brand extension process of China time-honored brand, 1) perceived risk transmits effects of brand trust to brand extension success; 2) perceived risk transmits effects of perceived fit to brand extension success. These discoveries underscore the importance of considering consumers' perceived risk in the formulation and implementation of brand extension strategies. This study contributes to understanding the causal relationships and impacts of perceived risk in the brand extension of time-honored brands. The empirical evidence provided can serve as a reference for the development of extension strategies and marketing management for China time-honored brands and other heritage brands.